2019
DOI: 10.1021/acs.chemmater.9b03245
|View full text |Cite
|
Sign up to set email alerts
|

Layered Oxide Cathodes for Li-Ion Batteries: Oxygen Loss and Vacancy Evolution

Abstract: Loss of oxygen in layered transition-metal oxides is a major reason for the structural degradation and thus the fade of electrochemical performance in the cathodes for Li-ion batteries. Via in situ transmission electron microscopy observations of LiNi 0.80 Co 0.15 Al 0.05 O 2 (NCA), we found that the oxygen loss in the layered cathode is a twostage process with distinct release rates. The initial rapid oxygen loss generates a high concentration of oxygen vacancies, which results in the formation of an amorphiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
91
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(110 citation statements)
references
References 60 publications
8
91
0
Order By: Relevance
“…13c ). Formation of the spinel phase may indicate oxygen evolution in order to form a cation densified state, according to previously reported literature 57 . Meanwhile at a low temperature (−173 °C), the resistance to amorphization of Na 2/3 Fe 1/2 Mn 1/2 O 2 decreases significantly (Supplementary Fig.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…13c ). Formation of the spinel phase may indicate oxygen evolution in order to form a cation densified state, according to previously reported literature 57 . Meanwhile at a low temperature (−173 °C), the resistance to amorphization of Na 2/3 Fe 1/2 Mn 1/2 O 2 decreases significantly (Supplementary Fig.…”
Section: Resultssupporting
confidence: 74%
“…The preferential defect alignment is likely due to the formation of interstitial-type dislocation loops in the interlayer space between transition metal layers, in which a large free volume is available to accommodate the accumulation of the interstitials. Such dynamics of defect evolution (e.g., the formation and accumulation of vacancies and interstitials) under ion irradiation shares similar attributes to that of defect evolution in layered cathodes on electrochemical cycling (e.g., vacancies and interstitials formation through oxygen evolution and ion migration) 57 , 84 , 85 . Point defects such as vacancies and interstitials can largely influence the electrochemical performance of layered cathodes.…”
Section: Discussionmentioning
confidence: 74%
“…Via in situ transmission electron microscopy observations of delithiated NCA cathode during heating, Zhang et al found that the oxygen loss in the layered cathode is a twostage process with distinct release rates, which includes rapid oxygen loss and formation of oxygen vacancies in the surface and further slow coalescing of atomic oxygen vacancies in the bulk. [32] Besli et al further probed the thermal decomposition, fracture, and oxygen evolution of chemically delithiated NCA particles during heating from room temperature to 450 °C using a number of advanced X-ray and electron probes. They have observed similar phenomenon as that occurred in the electrochemically delithiated NCA cathodes during heating, but further found that the release of oxygen also created numerous mesopores, which could thus provide a pathway for the release of lattice oxygen from the bulk and surface.…”
Section: O 2 Evolution From Ni-rich Cathodesmentioning
confidence: 99%
“…found that the oxygen loss in the layered cathode is a two‐stage process with distinct release rates, which includes rapid oxygen loss and formation of oxygen vacancies in the surface and further slow coalescing of atomic oxygen vacancies in the bulk. [ 32 ] Besli et al. further probed the thermal decomposition, fracture, and oxygen evolution of chemically delithiated NCA particles during heating from room temperature to 450 °C using a number of advanced X‐ray and electron probes.…”
Section: The Degradation Pathway Of Ni‐rich Layered Cathodes Under Hamentioning
confidence: 99%
“…Although Li‐rich transition metal oxides offer absorbing features, disadvantages in terms of low initial coulombic efficiency, continuous voltage decay, gas evolution and poor rate capability can't be ignored, which greatly hinder the practical applications of these cathode materials. [ 8‐12 ] The ratio of discharge capacity to charge capacity during the first cycle, namely initial coulombic efficiency, is ascribed to excessive irreversible Li + ions consuming. Transition metal (TM) ions have an increasing tendency to occupy lithium vacancies in high state of charge to form reconstruction, giving rise to the hindrance for lithium diffusion.…”
Section: Introductionmentioning
confidence: 99%